President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2020)
Happy Year of the Nurse! 2020 has officially been designated the Year of the Nurse/Midwife and we are all so proud to be part of such a prestigious profession dating back to 1860 when Florence Nightingale opened the first school of nursing at St. Thomas’ Hospital in London, England. While many things have changed, since 1860, some things have not. Nurses today are, as they were in Nightingale’s time, very aware of the environment they work in and the effect it has on their patients. Nurses now, as then, continue to serve at the forefront of advocating for patients and supporting families in times of crisis and ill health, for promoting cleanliness and healthy lifestyles, and for ensuring patient dignity in illness and in death. Bravo and thank you all for everything you do!